Antimicrobials Influence Bond Stiffness and Detachment of Oral Bacteria. (July 2016) - Song, L.; Hou, J.; van der Mei, H.C.; Veeregowda, D.H.; Busscher, H.J.; Sjollema, J.
Oral biofilm can never be fully removed by oral hygiene measures. Biofilm left behind after brushing is often left behind on the same sites and exposed multiple times to antimicrobials from toothpastes and mouthrinses, after which removal becomes increasingly difficult. On the basis of this observation, we hypothesize that oral bacteria adhering to salivary conditioning films become more difficult to remove after adsorption of antimicrobials due to stiffening of their adhesive bond. To verify this hypothesis, bacteria adhering to bare and saliva-coated glass were exposed to 3 different mouthrinses, containing chlorhexidine-digluconate, cetylpyridinium-chloride, or amine-fluoride, after which bacterial vibration spectroscopy was carried out or a liquid-air interface was passed over the adhering bacteria to stimulate their detachment. Brownian motion–induced nanoscopic vibration amplitudes of 4 oral streptococcal strains, reflecting their bond stiffness, decreased after exposure to mouthrinses. Concurrently, the percentage detachment of adhering bacteria upon the passage of a liquid-air interface decreased after exposure to mouthrinses. A buffer control left both vibration amplitudes and detachment percentages unaffected. Exposure to either of the selected mouthrinses yielded more positively charged bacteria by particulate microelectrophoresis, suggesting antimicrobial adsorption to bacterial cell surface components. To rule out that exposure of adhering bacteria to the mouthrinses stimulated polysaccharide production with an impact on their detachment, Fourier transform infrared spectroscopy was carried out on bacteria adhering to an internal reflection element, prior to and after exposure to the mouthrinses. Infrared absorption band areas indicated no significant change in amount of polysaccharides after exposure of adhering bacteria to mouthrinses, but wave number shifts demonstrated stiffening of polysaccharides in the bond, as a result of antimicrobial adsorption to the bacterial cell surface and in line with changes in surface charge. Clinically, these findings suggest that accumulation of oral biofilm exposed to antimicrobials should be prevented (interdental cleaning aids, floss use), as removal becomes progressively more difficult upon multiple exposures.